(untitled) (Research, Society and Development, 2021)
Açaí is a palm tree native to the Amazon region, occurring in lowland and highland areas. A socioeconomic survey and an estimate of the production and self-consumption of açaí producers in the municipality of Igarapé-Miri, in Pará, were carried out. In July and August 2019, 61 riverine producers from the Anapú, Caji and Meruú communities were interviewed. The average income is 1 to 2 minimum wages per month. The most governement transfers received by riverside dwellers are Bolsa Família and retirement. It was observed that the production of fruits per family was 36,139.98 kg, being 22,238.61 kg in the harvest and 13,901.38 kg in the off-season. It is noteworthy that the açaí consumed by riverside dwellers represents 16% of total production, with 10% in the harvest and 6% in the off-season. During the harvest, family members consume an average of 7.46 liters of thick açaí/day, while in the off-season the average consumption is 8.07 liters of fine açaí/day. Cassava flour, fish and some industrialized products are part of the diet together with açaí.